Relação CTS no contexto da formação inicial de professores no curso de Pedagogia - Ferst, Enia Maria (2016)
To present thesis treats of the teachers' initial formation, specifically in the Course of Pedagogy, in what it involves the relation Science, Technology and Society-STS in the context of that formation. To discuss the teacher's formation requests reflection and critical sense to look the context of that process aiming to contribute to improve it. For the development of this thesis it intended as general objective: To investigate as how occurs the relation STS in the ethics, epistemological and ontological dimensions in the process of teachers' initial formation in the Course of Pedagogy, starting from the reflexive teacher's tendency. The study was developed with the effective teachers of the Course of Pedagogy of the State University of Roraima - UERR. The data were collected through interviews and analysis of the Pedagogic Project of the Course (PPC) of Pedagogy. The research is of qualitative stamp, with the use of the Based Theory (BT) of Charmaz (2009) and the Analysis of Content of Bardin (2011) as methodological course. In the development of the thesis the glance of the theoretical ones is brought: Habermas, Heidegger, Vieira Pinto and Freire in the Science, Technology and Society, considering that these discuss those subjects in a critical perspective, what aids in the discussion of the interrelations STS in the context of the teachers' initial formation. The STS movement is presented with a short historical, the dialogues in the discussions between STS and the education and researches of STS and the Course of Pedagogy. They come the approaches of the reflexive teacher's formation and the focus STS and researches in Brazil on the reflexive teacher and the Course of Pedagogy. In the topic of the context of the research and methodological course is presented the characterization of the subject of the research, the process of analysis of PPC and the Based Theory (BT) as research method and the code process is demonstrated from the data to the light of the Theory Based with the strategy of the code initial line to line, the focalized code and the theoretical code of the which it rose the provisional categories to the conceptual categories The results are presented starting from the three conceptual categories: The ethics, epistemological and ontological dimensions in the teachers' initial Formation; The Educator’s Formation: the Science, the Technology and the Pedagogy and The relation STS in the curriculum of the educator's formation. Among the results of the research it stands out that the trainer teachers of the Course understand some of the present formative deficiencies in the formation, they demonstrate the need to enlarge the discussion in Collegiality of the Course in what it plays to the study of ST, they indicate that the Course of Pedagogy of UERR presents in a superficial way the interrelations of STS in the educator's formation, needing to be contextualized and enlarged for assisting the demands of that formation. It was verified that the PPC of the Course needs to be updated for best to assist the Teaching of Sciences in attendance to the deepened study of the focus STS and for that the inclusion of the Didacticism of the Sciences is indicated in the curriculum and of innovative practices that prioritize the critical, reflexive and contextualized teacher in the teachers' initial formation. For this to happen it is necessary to the discussion of the ethics, epistemological and ontological dimensions in relation to the Science as a program of teachers' initial formation.